2012
DOI: 10.1002/anie.201203255
|View full text |Cite
|
Sign up to set email alerts
|

A Sulfur Tripod Glycoconjugate that Releases a High‐Affinity Copper Chelator in Hepatocytes

Abstract: International audienceReleased in the cell: Three N-acetylgalactosamine units, which recognize the asialoglycoprotein receptor, were tethered through disulfide bonds to the three coordinating thiol functions of a sulfur tripod ligand that has a high affinity for CuI (see scheme). The resulting glycoconjugate can be considered as a prodrug, because after uptake by hepatic cells the intracellular reducing glutathione (GSH) releases the high-affinity intracellular CuI chelator

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 28 publications
1
57
0
Order By: Relevance
“…Conversely, the chelation of copper with high affinity ligands might offer avenues for the treatment of diseases associated with copper overload such as Alzheimer’s and Wilson’s disease. 55 Most importantly, we anticipate that these reagents will facilitate the reliable measurement of Cu(I) binding affinities of metalloproteins and other biologically relevant Cu(I)ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the chelation of copper with high affinity ligands might offer avenues for the treatment of diseases associated with copper overload such as Alzheimer’s and Wilson’s disease. 55 Most importantly, we anticipate that these reagents will facilitate the reliable measurement of Cu(I) binding affinities of metalloproteins and other biologically relevant Cu(I)ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Mintz and Delangle have exploited the tripodal architecture of a ligand to design a triantennary glycoside cluster system. 67 Experimental data have demonstrated that this system is also efficiently delivered to the hepatocytes. Furthermore, the glycoconjugate is not a Cu + chelator but the reduction by gluthatione converts it into an efficient chelator, which exhibits an affinity for Cu + as high as that of metallothioneins.…”
Section: Other Prochelatorsmentioning
confidence: 94%
“…The tripodal, disulfide-protected prochelator is reduced intracellularly to generate a high-affinity Cu(I) chelator (Figure 4e). [38,39]…”
Section: Passivating Metal Reactivity By Triggering Prochelatorsmentioning
confidence: 99%